The wine in the Paedagogus by Clement of Alexandria (Circe de clásicos y modernos, 2018)
In the second book of the Paedagogus, Clement thinks about the topic of wine, the corporal effects of its ingestion and its idolatrous reach by the opposition of two poles: curative remedy and prejudicial drug. We will analyze in the text of the Alexandrian the prescriptions in the use of wine reasoned from the dispositions of Paul’s discourse, and the way in which the ideas transmitted by previous and contemporary authors to this writer not only coincide with those developed by Clement, but also remain in an ambiguous position that oscillates between the acceptance of wine and its curative properties, and the rejection of its excessive or idolatrous use.
Keywords: wine; Clement; Alexandria; remedy; drug